2018
DOI: 10.1177/2156759x19870794
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors’ Use of Technology for Program Management

Abstract: The use of technology in school counseling remains largely underinvestigated. In this descriptive study, researchers surveyed school counselors to examine ways in which they are using technology to manage their programs. Findings indicate that technology is underutilized by school counselors and is more likely to be used for program management tasks in the area of organization than for communication with and presentation of information to stakeholder groups. We discuss implications for practice, preparation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
0
15
1
2
Order By: Relevance
“…With 48% of school counselors reporting using social media to connect with other school counselors either daily or weekly (Mason et al, 2019), we were unsurprised to see in our study that school counseling social media spaces topped the list of media where school counselors sought professional information. However, the percentage of school counselors in our study who reported reading from school counseling social media spaces weekly was nearly double the percentage of school counselors indicating weekly social media use to reach other school counselors in the Mason et al (2019) study. Similarly, about half of our participants indicated reading a school counseling blog in the past week, with another 29% reading school counseling blogs in the past month.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…With 48% of school counselors reporting using social media to connect with other school counselors either daily or weekly (Mason et al, 2019), we were unsurprised to see in our study that school counseling social media spaces topped the list of media where school counselors sought professional information. However, the percentage of school counselors in our study who reported reading from school counseling social media spaces weekly was nearly double the percentage of school counselors indicating weekly social media use to reach other school counselors in the Mason et al (2019) study. Similarly, about half of our participants indicated reading a school counseling blog in the past week, with another 29% reading school counseling blogs in the past month.…”
Section: Discussionmentioning
confidence: 83%
“…Bauman's survey measuring research confidence, relevance, and value confirmed previous work on school counselors' relationship with research and set the stage for the current investigation. Moreover, the 2004 study predates contemporary online materials including social media and blogging platforms (e.g., Facebook, Twitter) that school counselors now frequent, with approximately 24% of school counselors reporting using social media to communicate with other school counselors daily and 24% doing so at least weekly according to one study (Mason et al, 2019). As such, the school counseling field needs to better understand how these platforms have made their way into school counselors' professional information-seeking practices.…”
Section: School Counselor Perspectives On Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of ICT is necessary for the implementation of counseling services (Beidoglu et al 2015). In schools ICT can optimize operational efficiency and manage workloads more efficiently (Hayden et al 2008), ICT reduce costs and offer increased service delivery. ICT improve access to a broader audience and increase networking, cooperation and coordination capacities.…”
Section: Introductionmentioning
confidence: 99%
“…School counselor or called guidance and counseling teacher required to innovate in implementing counseling services using technology, especially during covid-19 pandemic. Unfortunately there are difficult situation, counselors do not optimally utilize technology for counseling services (Glasheen & Campbell, 2009;Mason et al 2018) and that they use it more for school administration than for communicating with stakeholders (Mason et al 2018). Several studies showed that school counsellors did not accept that ICT usage would increase service quality (Adebowale & Popoola, 2011;Cabaniss, 2001).…”
Section: Introductionmentioning
confidence: 99%